The first record of Robackia Seather (Diptera: Chironomidae) from Peninsular Malaysia - Ahmad , A.K.; Abd Aziz , Z.; Shuhaimi-Othman, M. (Pusat Sistematik Serangga ,UKM, 2013)
The first record of Robackia sp is described from upstream of Langat River Selangor, Malaysia by its larval. This genus characterized having seven segmented antennae and with modified mandible's inner teeth. It has 14 toothed mentum and coarse ventromental plate. An improved key to larvae of Robackia from Wiederholm (1983) is provided.